2018
DOI: 10.1007/s00198-018-4409-9
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s disease and the risk of osteoporotic vertebral compression fracture: a nationwide population-based study

Abstract: Patients with PD had significantly increased risk of osteoporosis and OVCF. Surgical treatment for OVCF in PD patients was associated with a better prognosis than conservative treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…There is accumulating evidence that the PD patients have an increased prevalence of osteoporosis and osteopenia [82][83][84], and PD is recognized as a cause of secondary osteoporosis [85]. In a study conducted in Korea, researchers found that 6542 (18.3%) of 35,663 PD patients experienced osteoporosis, and that fractures occurred most commonly within 6 months after PD onset and decreased after 3 years from PD diagnosis [86].…”
Section: The Relationship Between Vitamin D Level and Clinical Manifementioning
confidence: 99%
“…There is accumulating evidence that the PD patients have an increased prevalence of osteoporosis and osteopenia [82][83][84], and PD is recognized as a cause of secondary osteoporosis [85]. In a study conducted in Korea, researchers found that 6542 (18.3%) of 35,663 PD patients experienced osteoporosis, and that fractures occurred most commonly within 6 months after PD onset and decreased after 3 years from PD diagnosis [86].…”
Section: The Relationship Between Vitamin D Level and Clinical Manifementioning
confidence: 99%
“…Although in a young healthy individual, a fall from standing height would not likely result in a fracture, in PD, reduced bone mineral density (150)(151)(152) and a higher frequency of falls increase fracture risk (43,(153)(154)(155)(156)(157)(158)(159) . Studies suggest that in PD, osteoporosis and fracture are twice as likely (150,160,161) , and in women, PD is the strongest single contributor to fracture risk (162) .…”
Section: Malnutrition Muscle and Bonementioning
confidence: 99%
“…A meta-analysis showed an increased risk of fracture of 2 to 3 times in PD patients compared to controls 9 . A nationwide population-based study found a significantly increased risk of osteoporosis (hazard ratio 1.32) and surgery for OVC (hazard ratio 2.69) in PD patients compared to non-PD subjects 10 . Weight loss and sarcopenia are common in PD patients and correlate with greater motor changes, a higher rate of fall, and disease progression 11 .…”
Section: Discussionmentioning
confidence: 98%